Postharvest Technology Acceptance at the Handling and Storage Level among Fruit Vegetable Farmers in East Coast Economic Region (ECER) - Maizatul Vanisha Masril (2019)
Postharvest technology can help not only the yield of a farmers and also the productivity of a country. There are lots of postharvest technology that already being introduce to the farmer including the fruit vegetables farmers in East Coast Economic Region (ECER). But, the percentage of postharvest losses are still high and increasing each year. Although the phenomenon of new postharvest technology acceptance has been well appreciated, the increasingly characteristics phenomenon of the technology rejection are yet to be understand and studied. This research objectives are to identify postharvest technology acceptance towards postharvest technology acceptance at the handling and storage level among fruit vegetables farmers in ECER. A structured questionnaire was designed based on combinations of Technology Model Acceptance (TAM) and Theory of Planned Behavior model in this study. A purposive sampling technique was adapted and 105 fruit vegetables in ECER was involved in this study to answer the questionnaire. The data collected were entered and analysed using SPSS version 21.0. The analysis used was Descriptive statistics, Normality Test, Spearman’s Correlation and Reliability test. The independent variable in this study are perceived usefulness, perceived ease of use, and attitude while the dependant variables is postharvest technology acceptance in processing and storage level on fruit vegetables farmers in ECER. From this study, the results indicate that fruit vegetable farmers in ECER accept the postharvest technology but do not use and apply it as the correlations is significant but negligible. This study will be important researchers and farmers to understand the factors of postharvest technology acceptance besides in order to help reducing the postharvest losses.